Exploratory factor analysis: Validity and reliability of teacher's knowledge construct instrument - Abdol Jani, Wan Nur Fuziana; Razali, Fazilah; Ismail, Normala; Ismawi, Nurkhuzaizah (Human Resource Management Academic Research Society, 2023)
The study aims to determine the instrument's validity and reliability in measuring the construct of teachers' knowledge. The cross-sectional survey research design used a quantitative approach, with pilot study data obtained from 100 primary school teachers of the Trust School Programmed in Selangor, Malaysia. The selection of the samples was based on a two-stage random sampling strategy. In this study, the teacher's knowledge instrument was used to measure teachers’ knowledge in implementing a cooperative learning structure. The Exploratory Factor Analysis (EFA) procedure was employed to identify the factor loading value of each item, as well as the number of components for the teacher's knowledge construct. The EFA results demonstrate three components for the construct of teacher knowledge with the eigenvalue of each component exceeding 1.0, i.e., content knowledge, pedagogical knowledge and technological knowledge. The reliability of the content knowledge component was 0.966, of the pedagogical knowledge component was 0.967 and of the technological knowledge component was 0.961. The total construct of the teacher's knowledge was 0.967. The entire construct of teachers’ knowledge achieved the requirements for the validity and reliability of the construct. The study’s instruments can be used by other researchers to measure the construct of teachers' knowledge in other contexts.